2007
DOI: 10.3171/spi.2007.6.6.5
|View full text |Cite
|
Sign up to set email alerts
|

Cortical reorganization in patients with cervical spondylotic myelopathy

Abstract: Object Recent investigations have demonstrated that the cerebral cortex can reorganize as a result of spinal cord injury and may play a role in preserving neurological function. Reorganization of cortical representational maps in patients with cervical spondylotic myelopathy (CSM) has not been previously described. The authors sought to determine the feasibility of using functional magnetic resonance (fMR) imaging in patients with CSM to investigate changes in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
89
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(106 citation statements)
references
References 30 publications
13
89
1
3
Order By: Relevance
“…1,18 In one of the earliest studies in which functional imaging was used to assess cortical reorganization in CSM, Holly et al 23 demonstrated expansion of the cortical representation of the affected extremity (involvement of adjacent motor territories, the SMA, and bilateral cortical recruitment) before surgery in 4 patients, and surgical decompression resulted in improvements in neurological function and reorganization of the representational map.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,18 In one of the earliest studies in which functional imaging was used to assess cortical reorganization in CSM, Holly et al 23 demonstrated expansion of the cortical representation of the affected extremity (involvement of adjacent motor territories, the SMA, and bilateral cortical recruitment) before surgery in 4 patients, and surgical decompression resulted in improvements in neurological function and reorganization of the representational map.…”
Section: Discussionmentioning
confidence: 99%
“…19 Some studies have shown adaptive changes in bilateral primary motor cortex (M1), supplementary motor area (SMA), premotor area (PMA), cingulate motor area, parietal cortex, and contralateral primary somatosensory cortex (S1) in cases of SCI [8][9][10][11][27][28][29]33,40 and cervical compressive myelopathy due to spondylosis. 13,14,23,38 In this study we aimed to understand the cortical changes that occur due to CSM and following CSM surgery and to correlate these changes with functional recovery by using functional MRI (fMRI). We hypothesized that the recovery of normal activation patterns might coincide with clinical improvement.…”
mentioning
confidence: 99%
“…One possible explanation is that neurons experience synaptic modification in which preexisting connections develop new circuitry to restore lost function. 12 Results from the current study demonstrate that despite successful surgical decompression and clinical recovery, NAA levels decline, suggesting not only neuronal impairment, but also, more specifically, dysfunction in neuronal mitochondria. 5,6 Although this study reveals that metabolite level changes can be detected in both the motor and sensory cortices, future studies are needed to determine whether the temporal decreases in absolute NAA levels are the trigger for the recruitment of surrounding cortex and/or if decreasing NAA levels are a consequence of decreased metabolic demand due to cortical reorganization in which adjacent neurons are now incorporated into primary circuitry.…”
Section: Discussionmentioning
confidence: 92%
“…8,12 The exact trigger of cortical reorganization in adjacent neurons remains unclear. One possible explanation is that neurons experience synaptic modification in which preexisting connections develop new circuitry to restore lost function.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, expanded cortical activation was detected in patients with CSM. 48 The enhanced fMRI response of myelopathic cord might be the result of more neurons and synapses involved in performing neurological activity, corresponding to the increased area of cortical activation. Our current result also, interestingly, showed a significant linear correlation of increased BOLD signals with decreased FA and increased RD value in myelopathic cord.…”
Section: Methodological Considerations and Spinal Bold Response Relatmentioning
confidence: 99%